2011
DOI: 10.1517/13543784.2011.625011
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol for the treatment of heart failure

Abstract: Nebivolol is a β-blocker with distinctive characteristics. Initiated at 1.25 mg and titrated up to 10 mg/day, it has shown safety and efficacy in one large outcome trial, when added to standard medical therapy, in elderly patients (≥ 70 years) affected by HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…The (+)‐isomer provides the β1 blocking property, and both (+)‐ and mainly (‐)‐nebivolol have an endothelial NO‐dependent vasodilating effect by the l ‐arginine/NO pathway . (‐)‐Nebivolol increases the activity of the endothelial isoform of NO synthase (NOS) through a direct β3‐adrenoceptor agonistic effect .…”
Section: Discussionmentioning
confidence: 99%
“…The (+)‐isomer provides the β1 blocking property, and both (+)‐ and mainly (‐)‐nebivolol have an endothelial NO‐dependent vasodilating effect by the l ‐arginine/NO pathway . (‐)‐Nebivolol increases the activity of the endothelial isoform of NO synthase (NOS) through a direct β3‐adrenoceptor agonistic effect .…”
Section: Discussionmentioning
confidence: 99%
“…To determine the target ADR for analysis, we searched the most common ADRs based on literature and the label from the FDA official website. The most common AEs were headache, dizziness, nausea, diarrhea, tiredness, and bradycardia, of which bradycardia, nausea, and headache may lead to discontinuation ( Riva and Lip, 2011 ; Hanif et al, 2023 ). We mapped the above ADRs to their primary system organ class (SOC) according to MedDRA 26.0, mainly involving nervous system disorders, gastrointestinal disorders, and cardiac disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Less blockade of peripheral β 2 -adrenoceptors with a selective agent reduces the likelihood feelings of cold in the extremities [16][17][18] Controlled clinical trials of bisoprolol (vs. lisinopril [19]) and nebivolol (vs. metoprolol [20]) have demonstrated effective BP lowering, and no cause for concern regarding worsening of limb ischaemia Glycaemic control Many reports have described a worsening of glycaemic control during treatment with a β-blocker and use of a cardioselective agent helps to minimise these effects [17,18] The clinical significance of this phenomenon may have been overrated, however, worsened glycaemia may be unrelated to β-blockade [21],,and use of a β-blocker in a large diabetes prevention trial was not associated with increased risk of diabetes [22] Bisoprolol or nebivolol has not been associated with worsening of glycaemia [7,[23][24][25][26][27][28][29] Asthma and COPD Bronchospasm in patients with COPD or asthma may be exacerbated by blockade of β 2 -adrenoceptors in the smooth muscle of the airways [30] Non-selective β 1 -blockers, but not β 1 -selective agents, increase the risk of asthma exacerbations [31] A recent (2020) randomised, double-blind, crossover study confirmed that the bronchodilatory effects of bisoprolol were non-inferior during treatment with bisoprolol vs. placebo [32] Such findings have led to a reappraisal of the use of selective β 1 -blockers in patients with asthma or COPD [30,33]; β 1selective agents are no contraindicated in Europe only for "severe bronchial asthma" Erectile function β-blockers, have been associated with new or exacerbated erectile dysfunction [34], although neither bisoprolol nor nebivolol were associated with sexual dysfunction [35][36][37] Nebivolol improved erectile function vs. metoprolol [38,39], or atenolol (± chlorthalidone) [40] Another study demonstrated fewer patients reporting vs. not reporting sexual dysfunction on nebivolol vs. other β-blockers…”
Section: Peripheral Vasoconstriction and Pvdmentioning
confidence: 99%
“…β-blockers, have been associated with new or exacerbated erectile dysfunction [ 34 ], although neither bisoprolol nor nebivolol were associated with sexual dysfunction [ 35 – 37 ]…”
Section: Properties Of Bisoprolol and Nebivololmentioning
confidence: 99%